Anaerobic Digestion of Starch Wastewater: the Effect of pH and Oxidation Reduction Potential on the Reactor Performance - Zangta Sang; Chayanon Sawatdeenarunat; Pitchaya Suaisom (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
Anaerobic digestion (AD) of starch wastewater for biogas production has been widely installed in Thailand for a decade. Unfortunately, this specific waste stream contains low alkalinity (Alk) and high volatile fatty acids (VFAs) which could easily lead to system instability. The appropriate monitoring indicators could help to decrease chance of reactor failure. The aim of this study is to investigate the performance of the AD system and the effect of operating parameters i.e. oxidation-reduction potential (ORP) and pH on the system in a continuous stirred tank reactor operated in semi-continuous mode at organic loading rate (OLR) of 1.0 kg COD/m3.day. The temperature was controlled at a mesophilic condition (35±2°C) for the whole experiment. The results showed that the average ORP and pH were -400 ±50 mV and 7.0 ± 0.2, respectively. The average biogas and methane yields were 0.901±0.128 NL/g VS added and 0.528±0.076 NL/g VS added, respectively. The methane composition was 58.43±4.76 %. The total COD and filtrated COD removal efficiencies were 94.75±1.42% and 97.88±0.53%, respectively. It could be concluded that at the low OLR (i.e. 1.0 kg COD/m3.day), pH and ORP was stable and fell within the recommended range for AD and indicated the stability of the system.